Biomass accumulation and partitioning in cacao (Theobroma cacao Linn.) as affected by age, fertilizer application and canopy exposure - Ajibona, O.A. (2023)
Cacao is a plant known widely for its beans used in the production of chocolate and cocoa powder. Biomass production dynamics in cacao is an important process that needs to be understood for best management practices that guarantee maximum bean yield. This study investigated the accumulation and distribution of biomass in cacao as affected by age, fertilizer application and canopy exposure at the Cocoa Research Institute of Nigeria (CRIN) (7.36oN, 3.85oE) and the International Institute of Tropical Agriculture (IITA) (7.49oN, 3.90oE) in Ibadan, Oyo state, Nigeria in 2020. Principal Component Analysis was used as a selection tool to ensure that the trees used for the study fairly represented the whole plot. Fertilizer (300g of N.P.K 15:15:15 per tree) was applied using ring method to half of the selected trees while the other half had no fertilizer application. Split plot design was used with three replicates. A total of 18 trees of 8, 12 and 47 year old were harvested and measured. Data collected on shoot, root and leaf parameters were subjected to Analysis of Variance and means were separated using Least Significant Difference at 5% probability level. Regression analysis was carried out to establish allometric relationship between non-destructively obtained plant parameters (stem diameter, mean canopy diameter, height) and the total tree biomass and the biomass of specific tree organs. The age of the tree had significant effect on height (534.90 cm, 723.90 cm and 735.8 cm), leaf fresh weight (2.75 g/leaf, 2.99 g/leaf and 4.07 g/leaf) and leaf dry weight (1.22 g/leaf, 1.35 g/leaf and 1.88 g/leaf) of the 8-year, 12-year and 47-year old trees, respectively. Fertilizer application influenced total dry biomass of leaves (6.36kg/tree), leaf fresh weight (3.47 g/leaf) and leaf dry weight (1.58 g/leaf) with the non-fertilized trees having the highest values irrespective of their position in the canopy. Biomass accumulation in the leaves and branches decreased from 14-4% and 48-36% respectively. However, stem biomass increased from 20-33% and root biomass was maintained at 20% for the 8-year, 12-year and 47-year old trees. The highest contributor to total biomass were in the order of branch > stem > roots > leaves. The allometry between the components and the whole cacao revealed that the best predictor of biomass was stem diameter (R2 = 0.634-0.872). The position of the leaf in the canopy was discovered to have a significant effect on Specific Leaf Area (SLA) with leaves in the lower canopy portion of the tree showing a higher SLA than those in the upper portion. Leaf production in cacao was influenced jointly by their position in the canopy and exposure to sunlight. It was concluded that biomass accumulation increased with tree age and the woody organs were the major contributors to the total biomass. Stem diameter is recommended for use in predicting total biomass using allometric equation. Application of fertilizer to aged cacao trees is not recommended.